THE EFFECT OF SELF EFFICACY AND FRAUD DIAMOND ON FRAUDULENT BEHAVIOR ACADEMIC ACCOUNTING STUDENTS - Azzahroh, Fatimah; Suhendro; Fajri, Rosa Nikmatul (STIE Kusuma Negara, 2020)
Academic cheating behavior is an act that reflects dishonesty to get academic success. Factors that influence academic cheating are self efficacy and diamond fraud (pressure, opportunity, rationalization, and ability). The purpose of this study is to empirically examine the effect of self efficacy and diamond fraud on the academic cheating behavior of accounting students. The population in this study were students majoring in accounting in private universities (PTS) in Surakarta with a sample of 116. The type of research conducted was quantitative research. The type of data used is primary data. The analysis technique used is multiple linear regression analysis. The results showed that simultaneous self efficacy and diamond fraud affect academic cheating behavior, partially indicating that opportunities and abilities affect academic cheating, whereas self efficacy, pressure, and rationalization do not affect academic cheating. The benefits of this study are as a reference and reference for further research related to academic cheating behavior.